Keadilan Substantif dalam Penetapan Ganti Kerugian Pengadaan Tanah Proyek Jalan Tol Yogyakarta-Bawen di Kabupaten Magelang (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Infrastructure development as a National Strategic Project (NSP), such as the Yogyakarta-Bawen Toll Road, aims to improve public welfare but often faces a crucial issue in the land acquisition process, namely the determination of compensation. This research examines the application of substantive justice, which focuses not only on procedural compliance (procedural justice) but also on the fairness and adequacy of the final outcome for the entitled parties. Using a juridical-empirical approach, this article analyzes two main problems: first, how substantive justice is realized in the deliberation stage of determining compensation and what factors cause disagreement from residents. Second, how the overall stages of land acquisition affect the achievement of substantive justice and the obstacles encountered. The analysis shows that although the land acquisition stages have procedurally followed Law No. 2 of 2012, the achievement of substantive justice is still hindered. Factors such as the appraisal of compensation which is deemed not to cover non-physical losses, lack of transparency, and an imbalanced bargaining position in deliberations are the main causes of disagreement. Obstacles in the planning, socialization, and payment stages also impede the realization of a complete sense of justice for the affected communities. This study is expected to contribute to the development of land acquisition policies that prioritize fairness, transparency, and the protection of the rights of affected communities.